NEW PROPOSED GSI CLASSIFICATION CHARTS FOR WEAK OR COMPLEX ROCK MASSES - Marinos, P. V (Bulletin of the Geological Society of Greece, 2010)
The paper deals with the geotechnical classification of weak and complex rock masses. The complexity of these geological material demands a more specialized research and geological characterization due to the special features of their rock mass types regarding both their structure and their lithological characteristics. The weak and complex rock masses under consideration, often heterogeneous and containing rocks of extremely low strength, have in most cases undergone highly tectonised disturbance resulting in the destruction of their initial structure, while weathering can be another particular feature. The geotechnical types and their characterization of rock masses that can be developed in flysch, molasse, brecciated limestone, ophiolites and disturbed or weathered gneiss are studied here. In order to describe these masses in a quantitative way and provide numerical values to engineering design, new or revised rock mass classification diagrams are introduced within the general concept of the GSI system, or specific projections inside the existing GSI diagram are proposed The fundamental source for this research was data from the design and construction of 62 tunnels of Egnatia Highway appropriately assessed, processed, correlated and associated with field work.